Sucesos Estresantes de Vida en Jóvenes Adultos Estudiantes en Riohacha La Guajira, Descrito desde un Enfoque Diferencial (2023)
A life event is that event that forces a behavioral and cognitive response, that serves as a filter or is a driver of the development of a stressful activation by the subject or subjects and that generally implies a change. The objective of the research was to analyze the life events of the students of the Corporación Sin Fronteras in Riohacha from a differential approach. The 9 methodology is quantitative where the Stressful Life Events Test (Adolescent Version) by Gómez and Duran (2003) is applied. The study population was initially 120 people, however, due to test validity criteria and non-attendance for external reasons, A sample of 92 students from different technical-professional careers was drawn.